Effect of oral administration of the fresh juice of Bamboo (Bambusa vulgaris) young shoots on enumeration of bone marrow cells, platelets, splenocyte and phagocytic activity of peritoneal macrophages of rats - Nayanathara Thathsarani; Chanika D. Jayasinghe; Uthpala Jayawardena; Nayanakanthi Nilakarawasam (Elsevier, 2021)
Background: Fresh juice of young shoots of Bamboo is a traditionally acclaimed remedy against immune disorders and febrile illnesses. Though, many other therapeutic activities of Bamboo have been investigated, the immunomodulatory activity align with the traditional claim is yet to be scientifically validated. Purpose: The present study investigates the effect of fresh juice of Bambusa vulgaris (FJBV) young shoots, the Sri Lankan variety, on selected immune responses of rats, accompanied by the toxicological and phytochemical profiles. Method: Wistar rats (n = 6/group) were orally administered with 3 doses of FJBV - low dose (LD) 0.25 mL/200 g BW (Body Weight), human equivalent dose (HED) 0.5 mL/200 g BW and high dose (HD) 1 mL/200 g BW - once daily for 2 consecutive days according to the traditional treatment practice. Distilled water (DW) and Cyclophosphamide (2 mg/200 g BW) served as the negative and positive controls, respectively. The effect of FJBV on immune cell enumeration, cytokine levels, and phagocytic activity of peritoneal macrophages and serum antioxidant capacities were investigated using standard procedures. Further, the toxicity of FJBV was investigated to corroborate the safety of oral consumption. Chemical profile was also investigated qualitatively. Results: Oral treatment of FJBV for two consecutive days exhibited significant alterations in immune cell counts, phagocytic activity and serum antioxidant levels. Rat BM (Bone Marrow) counts were significantly reduced by both HED and HD (p < 0.05) while, platelet counts were significantly lowered only by HD of FJBV (p < 0.05). The neutrophil to lymphocyte ratio was significantly reduced by the LD of FJBV (p < 0.05), though the Differential WBC (White Blood Cells) counts were not altered by the FJBV oral treatment (p > 0.05). However, splenocyte (SC) counts were significantly increased by the HD (p < 0.05). The FJBV doses tested herein exhibited non-significant alteration in both serum pro and anti-inflammatory cytokine IFN gamma and IL-10, respectively.The phagocytic activity of peritoneal macrophages was significantly lowered by HED and HD (p < 0.05). The acute oral treatment of HD of FJBV for 14 days was found to be safe in terms of hepatic, renal and immune toxicities. Chemical profile revealed the presence of glycosides, reducing sugars, starch, proteins and saponins which may have led to the bioactivities of FJBV. Conclusion: : The present study provides affirmation of the traditional claim of the FJBV as an immunomodulatory preparation. Further studies are warranted to explicate the cytotoxic effect of FJBV, which could be a starting material for immunosuppressive drug development.